(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2023)
Body drawing has always been a current topic. In the past it was mainly linked to the figurative arts, nowadays it refers to all project fields in architecture, product design and fashion. Due to its transversal character, the body drawing has been the subject of both analog and digital representations. If the ways in which it was represented have adapted over time to technical and digital innovations, the geometric and proportional principles underlying the drawing of the human figure have remained almost unchanged. Precisely the permanence still today in the body digital modeling of the proportional relationships encoded starting from the Renaissance constitutes the interest from which this research begins. If in the Renaissance the principles for the representation of architectural spaces in artistic works were well known, the principles for the construction of the image of the human figures present in them were less debated by treatises. The paper analyzes in the context of the treatises of the time the section of the volume by Abraham Bosse in which the author introduces a method for drawing and also for the relief of the human body, synthesizing it with a knot scheme defined by the same author as “wire figure”. This scheme becomes the starting point to build graphically and with freehand drawing techniques the representation of anatomical shapes and therefore of the drapery of the dress worn. The graphic analysis compares the dimensions between the anatomical parts in the time and current measurement systems.